Composition and diversity of gut microbiota across developmental stages of Spodoptera frugiperda and its effect on the reproduction - Fu, Junrui; Wang, Junhan; Huang, Ximei; Guan, Boyang; Feng, Qili; Deng, Huimin (Frontiers in Microbiology, 2023)
Spodoptera frugiperda is a serious world-wide agricultural pest. Gut microorganisms play crucial roles in growth, development, immunity and behavior of host insects.Here, we reported the composition of gut microbiota in a laboratory-reared strain of S. frugiperda using 16S rDNA sequencing and the effects of gut microbiota on the reproduction. Proteobacteria and Firmicutes were the predominant bacteria and the taxonomic composition varied during the life cycle. Alpha diversity indices indicated that the eggs had higher bacterial diversity than larvae, pupae and adults. Furthermore, eggs harbored a higher abundance of Ralstonia, Sediminibacterium and microbes of unclassified taxonomy. The dynamics changes in bacterial communities resulted in differences in the metabolic functions of the gut microbiota during development.Interestingly, the laid eggs in antibiotic treatment groups did not hatch much due to the gut dysbacteriosis, and the results showed gut microbiota had a significant impact on the male reproduction. Our findings provide new perspectives to understand the intricate associations between microbiota and host, and have value for the development of S. frugiperda management strategies focusing on the pest gut microbiota.